APPLICATION OF FOREIGN EXPERIENCE IN THE ORGANIZATION OF MANAGEMENT COST ACCOUNTING (World Economics and Finance Bulletin, 2023)
The processes of transition to international financial reporting standards are highlighted
Keywords: Business language; international markets; economic indicators